2020
DOI: 10.3390/ma13081978
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Crystallographic Examinations of the Homoepitaxially Grown Rubrene Single Crystals

Abstract: Homoepitaxial growth of organic semiconductor single crystals is a promising methodology toward the establishment of doping technology for organic opto-electronic applications. In this study, both electronic and crystallographic properties of homoepitaxially grown single crystals of rubrene were accurately examined. Undistorted lattice structures of homoepitaxial rubrene were confirmed by high-resolution analyses of grazing-incidence X-ray diffraction (GIXD) using synchrotron radiation. Upon bulk doping of acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 61 publications
2
13
1
Order By: Relevance
“…Generally, the crystals were individually taken out in the ambient atmosphere for further processing to be prepared as specimens for the photoemission experiments as described in the previous paragraph. For maintaining the crystals ''intrinsic'' by avoidance of the exposure to the ambient conditions, 119,120 sample treatment in a glovebox directly connected with the PVT equipment, as illustrated in Fig. 12, is an efficient measure as discussed in Section III.1.…”
Section: Methods Of Overcoming Sample Charging Of An Electrical Insulamentioning
confidence: 99%
“…Generally, the crystals were individually taken out in the ambient atmosphere for further processing to be prepared as specimens for the photoemission experiments as described in the previous paragraph. For maintaining the crystals ''intrinsic'' by avoidance of the exposure to the ambient conditions, 119,120 sample treatment in a glovebox directly connected with the PVT equipment, as illustrated in Fig. 12, is an efficient measure as discussed in Section III.1.…”
Section: Methods Of Overcoming Sample Charging Of An Electrical Insulamentioning
confidence: 99%
“…In previous studies, highly ordered heteroepitaxial interfaces of uniformly aligned n-type molecular materials formed on single crystals of p-type organic semiconductors have been attained. 16 21 Moreover, it has been confirmed that single-crystalline thin films with extremely good crystallinity can be obtained by homoepitaxy, 22 24 where molecules are deposited on single-crystal substrates of the same molecular species. This methodology enables the realization of p–n homojunctions of a monolithic organic semiconductor single crystal by accurately controlled impurity doping.…”
mentioning
confidence: 97%
“… 21 , 48 The VB of RubSC also shifted slightly upward after the fmRub deposition; in other words, the E F moved toward the VB, implying the occurrence of acceptor doping to RubSC. 23 , 24 The suppression of the VB-derived peak of RubSC suggests the complete covering of the RubSC surface by the fmRub overlayer, at least at an fmRub thickness of 3 nm. It is noteworthy that this thickness was much greater than the probing depth (<1 nm) for UPS in the present measurement conditions 49 and was equivalent to the c -axis lattice constant (3.44 nm), which consists of two molecular layers of fmRub.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In the solution method, the types of solvents, concentration of rubrene and the temperature of crystal growth may all play an important role in which polymorph is formed. In addition to the above common methods for preparing rubrene single crystals, many novel methods have been developed in recent years, including epitaxy [36,37], microspating in air sublimation [38] and so on.…”
Section: (A)-(c))mentioning
confidence: 99%